2010
DOI: 10.1111/j.1740-8261.2010.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Pathologic, and Magnetic Resonance Imaging Characteristics of Canine Disc Extrusion Accompanied by Epidural Hemorrhage or Inflammation

Abstract: Our aim was to characterize the magnetic resonance (MR) imaging features of canine disc extrusion accompanied by epidural hemorrhage or inflammation. We correlated the imaging characteristics of this type of disc extrusion in 46 dogs and compared these features with clinical signs and pathologic findings. Data from 50 control dogs with MR imaging features of a disc extrusion with no associated hemorrhage or inflammation, characterized by a T2-hypointense extradural mass, were used for comparison of the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 19 publications
4
76
0
Order By: Relevance
“…1). The highest incidence of intervertebral disc disease was observed in dachshunds, and these findings are consistent with literature data (Besalti et al 2006, Mateo et al 2011, Suran et al 2011). The second most predominant spinal disorder was the Wobbler syndrome ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…1). The highest incidence of intervertebral disc disease was observed in dachshunds, and these findings are consistent with literature data (Besalti et al 2006, Mateo et al 2011, Suran et al 2011). The second most predominant spinal disorder was the Wobbler syndrome ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Not all studies included both T1WI and T2WI scans and postcontrast images. Conventional intervertebral disc herniation lesions have been described with various signal intensities and are often contrast enhanced in MRI studies because of secondary hemorrhage or inflammation and degeneration of the extruded nucleus pulposus . Retrospectively, readers for the current study reported that the T2WI hyperintense lesions seen in cases 1–3 seemed to be the “golf tee sign,” although this information was not available to surgeons before surgery.…”
Section: Discussionmentioning
confidence: 76%
“…Retrospectively, readers for the current study reported that the T2WI hyperintense lesions seen in cases 1–3 seemed to be the “golf tee sign,” although this information was not available to surgeons before surgery. A “golf tee sign” can be theoretically differentiated from other conditions by using a combination of T2WI, T2*WI, fluid‐attenuated inversion recovery (FLAIR), and pre‐ and post‐contrast T1WI, as well as the single‐shot turbo spin echo sequence or half‐Fourier acquisition single‐shot turbo spin‐echo pulse sequence . However, differentiation of these lesions using low‐field MRI is not easy in the canine vertebral canal due to the smaller size vs. humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because fat suppression techniques are useful in ascertaining the fatty characteristics of a mass [2,[4][5][6], the mass lesion in the present case was exactly defined by a fat suppression technique. Differential diagnoses for an MR image like that in the present case in which T1-and T2-weighted images showed hyperintense signals include hemorrhage, hematoma, and fatty tissue [1,[3][4][5][6]8]. Of these, a fat suppression image may be useful to distinguish the involvement of adipose tissue amongst other possible etiologies [2,[4][5][6].…”
mentioning
confidence: 98%
“…A CT image, however, is also able to detect fatty infiltration in the muscle area around the spinal cord as negative Hounsfield unit values [4,6]. Moreover, CT imaging is useful to detect destruction of the vertebral body, which is a common feature of infiltrative lipomas [3]. Another important issue in the differential diagnosis of the 2 diseases is planning the surgical strategy.…”
mentioning
confidence: 99%